Low temperature polymorphism in 3-amino-1-propanol - Cacela, C. (2003)
3-Amino-1-propanol (3AP) was investigated by differential scanning calorimetry, and low temperature powder X-ray diffraction and Raman spectroscopy. Within the range of temperatures studied (-150-25 °C), 3AP was found to be able to crystallize in two monotropic polymorphs. Fast cooling rates produce an amorphous state that, on heating, crystallizes into the metastable polymorph. At higher temperatures, this metastable crystalline phase converts into the stable crystal. Using intermediate cooling rates, 3AP crystallizes as the metastable polymorph, the solid[right triple arrow]solid transition leading to conversion of this form into the stable polymorph occurring during the subsequent heating. Slower cooling rates enable formation of the stable crystal on cooling. The two crystalline polymorphs were structurally characterized by powder X-ray diffraction and Raman spectroscopy. It was concluded that different conformations are assumed by the individual molecules of 3AP in the two crystalline varieties, with the molecules assuming the all-trans configuration in the metastable crystalline state and having the heavy atom backbone trans but the NH2 and OH groups gauche in the stable crystal.